Reconstruction of interactions in the ProtoDUNE-SP detector with Pandora - A. Abed Abud; B. Abi; R. Acciarri; M. A. Acero; M. R. Adames; G. Adamov; M. Adamowski; D. Adams; M. Adinolfi; C. Adriano; A. Aduszkiewicz; J. Aguilar; et al. (European Physical Journal C: Particles and Fields, 2023)
Abstract The Pandora Software Development Kit and algorithm libraries provide pattern-recognition logic essential to the reconstruction of particle interactions in liquid argon time projection chamber detectors. Pandora is the primary event reconstruction software used at ProtoDUNE-SP, a prototype for the Deep Underground Neutrino Experiment far detector. ProtoDUNE-SP, located at CERN, is exposed to a charged-particle test beam. This paper gives an overview of the Pandora reconstruction algorithms and how they have been tailored for use at ProtoDUNE-SP. In complex events with numerous cosmic-ray and beam background particles, the simulated reconstruction and identification efficiency for triggered test-beam particles is above 80% for the majority of particle type and beam momentum combinations. Specifically, simulated 1 GeV/c charged pions and protons are correctly reconstructed and identified with efficiencies of 86.1 $$± 0.6$$ ± 0.6 % and 84.1 $$± 0.6$$ ± 0.6 %, respectively. The efficiencies measured for test-beam data are shown to be within 5% of those predicted by the simulation.